Hibiscus sabdariffa tea improved the maximum oxygen uptake (VO2max) and blood pressure in normotensive participants - Syamsul Rahmat, Annisa Alpiani, Sri Adi Sumiwi, Leonardo Lubis, Jutti Levita, Ajeng Diantini (Journal of Applied Pharmaceutical Science, 2023)
The heavy physical practice may escalate the production of reactive oxygen species, which eventually results in cell damage. Previous studies announced that treatment with antioxidants might decrease oxidative stress caused by the physical practice. Studies on the ethanol and water extracts of Hibiscus sabdariffa calyces had proven their antioxidant activity. Our work is the first report on the effect of 30 days of daily intake of H. sabdariffa tea on the maximum oxygen uptake (VO2max) and blood pressure (BP) in healthy male and female normotensive participants. The VO2 max, measured to obtain the participants’ cardiovascular fitness status, was performed by following the Young Men’s Christian Association step test. Our study revealed that H. sabdariffa tea intake decreased the BP of the participants in week 4 and increased the number of participants with average VO2max status, starting from week 2 to 4, compared to baseline. Taking these results together, H. sabdariffa tea may be beneficial to improve the maximum oxygen uptake status in normotensive participants.